A new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the Rio Negro, Amazonas, Brazil: the smallest species of Potamotrygon - Carvalho, Marcelo R. De; Rosa, Ricardo S.; Araújo, Maria Lúcia G. De (Zootaxa, 2016)
A new species of Potamotrygon is described from the Rio Negro drainage, Amazonas, Brazil. In spite of being cited or pictured several times in the scientific and aquarium fish literature since the 19th Century, it had been misidentified and still lacked a scientific name. Potamotrygon wallacei, n. sp., is diagnosed by the following characters: dorsal surface of disc light brown, with black irregularly-shaped vermiculate markings forming an amphora- or Ω-shaped figure on mid-disc, delimiting light brown reniform areas at disc center, and with subcircular light brown ocellate markings on disc margins; small body size (smallest known Potamotrygon species; largest examined specimen measured 310 mm DW); dorsal spines on tail usually rather low, without broad bases, in one to rarely three irregular rows, but extending posteriorly only to tail mid-length and not to caudal stings, with altogether relatively few spines; denticles on posterior mid-disc and tail base Y-shaped, with a central, anterior, bulbous cusp and usually two posterior pairs of smaller, rounded cusps; and single (anterior) angular cartilage. The new species is similar to P. orbignyi and other "reticulated" species in having a single (anterior) angular cartilage and in the color pattern of the tail, but is easily distinguished based on its size, dorsal tail spine arrangement, and specific details of color pattern.